A neural basis for inference in perceptual ambiguity - Sterzer, Philipp (National Academy of Sciences, 2007)
When looking at ambiguous visual stimuli, the observer experiences frequent spontaneous transitions between two competing percepts while physical stimulation remains unchanged. Despite recent advances in understanding the neural processes underlying such perceptual rivalry, a key question has remained unresolved: Does perceptual rivalry result merely from local bistability of neural activity patterns in sensory stimulus representations, or do higher-order areas play a causal role by shifting inference and, thus, initiating perceptual changes? We used functional MRI to measure brain activity while human observers reported successive spontaneous changes in perceived direction for an ambiguous apparent motion stimulus. In a control condition, the individual sequences of spontaneous perceptual switches during bistability were replayed by using a disambiguated version of the stimulus. Greater activations during spontaneous compared with stimulus-driven switches were observed in inferior frontal cortex bilaterally. Subsequent chronometric analyses of event-related signal time courses showed that, relative to activations in motion-sensitive extrastriate visual cortex, right inferior frontal cortex activation occurred earlier during spontaneous than during stimulus-driven perceptual changes. The temporal precedence of right inferior frontal activations suggests that this region participates in initiating spontaneous switches in perception during constant physical stimulation. Our findings can thus be seen as a signature of when and where the brain “makes up its mind” about competing perceptual interpretations of a given sensory input pattern.